Taha Hussein and Abbas Mahmud al-Aqqad on the Greek Philosophy: A Comparative Study - Fouly, Nabil (DINIKA : Academic Journal of Islamic Studies, 2016)
Taha Hussein (1889-1973) and Abbas Mahmud al-Aqqad (1889-1964) are two prominent contemporary scholars in Egypt. This article delivered the comparison of both thoughts regarding to the Greek philosophy, while extensively influenced by the Greek philosophical tradition with two different responses. Thaha Husein so fascinated to the Greek philosophical traditions in which he developed appreciatively as found on his works. While al-Aqqad, he almost concerned on reviewing the value of the Greek philosophical tradition. His interaction to them feels more rigid because he used to accentuate his Arabian color and manifested his resistence when interacting with the Greek philosophical tradition. On several occasions, Al-Aqqad more often criticized them as compared to Thaha Husain. Well-known as westernized, Thaha Husain, instead of being uncritical of Greek philosophy, to him, the beginning of Greek philosophy formulation somehow indicated through their interaction with the Eastern culture. As said, East in the past became a source and reference, albeit limited to the physical aspect. While al-Aqqad, he viewed uncertainly whether Greek or East is the major source of the early emergence of philosophy as a scientific tradition.Keywords:Greek Philosophy, Islamic Philosophy, West, East